Piezoresistive characterization of graphene/metakaolin based geopolymeric mortar composites. (28th November 2017) - Lamuta, C.; Bruno, L.; Candamano, S.; Pagnotta, L.
Abstract: Geopolymers are recently developed ceramic materials produced by alkaline activation of thermally activated natural materials such as metakaolin. Due to their promising application in the field of structural components, the presence of a piezoresistive effect is a very useful property for such materials because it allows the real time self-monitoring of civil infrastructures. As observed for cement-based materials, the use of a conductive filler can enhance the piezoresistive response by avoiding measuring issues related to the electrical polarization. In this work we present preliminary results about the piezoresistive characterization of a metakaolin based geopolymeric mortar filled with graphene nanoplatelets. Composites with different graphene weight concentrations (0, 0.1, 0.5, 1%) were produced and the gauge factor (the ratio between the electrical resistance variation and the imposed strain) was calculated by means of dynamic four-probe resistance measurements. Very high gauge factor values (in the range of 1000-2000) were recorded and they can vary according to the dispersion quality of the graphene nanoplatelets into the ceramic matrix.